Interventional radiology training: a comparison of 5 English-speaking countries - Mandal, Indrajeet (Br J Radiol, 2020)
OBJECTIVE: To compare key characteristics of interventional radiology (IR) training in the UK with four other English-speaking countries (USA, Canada, Australia and New Zealand) and summarise requirements for training. METHODS: Main features examined were career pathway and requirements, examinations required, specific competition for IR and the process of applying for training as an international medical graduate. Data were collected from official governing body publications, literature and personal experience. RESULTS: Several differences were highlighted, including length of training (ranging from 6 to 9 years after medical school), length of IR-specific training (ranging from 1 to 3 years) and examinations required (USA and Canada have additional IR-specific examinations). The level of competition is generally high, in all countries. CONCLUSIONS: With the demand for IR services set to increase over the next few years, it is crucial that more IR specialists are trained to meet this demand. Awareness of training structures in other countries can highlight opportunity and pitfalls, and help ensure the number of highly trained interventional radiologists in the UK continues to grow.